Effect of 2,4-D sub-dose on the initial development of common bean crop - Rainieri Massucato, Luana; Mendes Pio de Oliveira, Guilherme; Libardoni, Gabriela; Ferreira Dominoni, Ana; da Costa, Silvano; Simões Azeredo Gonçalves, Leandro (Revista Ciência Agronômica, 2021)
The adoption of cultures tolerant to synthetic auxins can increase the occurrence of drift of these herbicides, interfering in the development of naturally sensitive cultures, such as beans. The aim of this study was to evaluate the germination and initial development of bean seedlings, using sub-doses of the herbicide 2,4-D. The design of experiment I was completely randomized, with eight treatments and four replications, except for germination, with eight replications. The seeds were sowed in 100 mL of water with concentrations of 0.0; 1.12; 2.14; 4.18; 8.37; 16.75; 33.50 and 67.00 g a.e. L-1 of 2,4-D. Germination, length, seedling fresh and dry mass and electrical conductivity were evaluated. The design of experiment II was completely randomized with five treatments and four replications. The beans were sowed in sand and then sprayed at concentrations of 0.0; 8.37; 16.75; 33.50 and 67.00 g e.a. L-1 of 2,4-D. Seed emergence, injury, fresh and dry shoot mass were evaluated. According to the regression analysis, there was a reduction in germination, regardless of the concentration used, as well as the seedling length. Seeds sown in this solution presented impaired root system and development, tending to mortality. Electrical conductivity increased as herbicide concentrations increased, indicating lower physiological potential of seeds. In experiment II, increasing 2,4-D concentrations reduced emergence and increased injury to bean plants. It is concluded that the sub-doses of the 2,4-D herbicide negatively affect the germination and initial development of bean seedlings.